Arbitrage and the Forward Gold Premium: Reply - Makin, John H. (Quarterly Journal of Economics, 1974)
Journal Article Arbitrage and the Forward Gold Premium: Reply Get access John H. Makin John H. Makin The University of Wisconsin — Milwaukee Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 88, Issue 3, August 1974, Pages 502–504, https://doi.org/10.2307/1881950 Published: 01 August 1974